An activity theory approach to fair assessment moderation in transnational education - Thuraisingam, Thavamalar; Kaur, P; Yeo, Shelley; Briguglio, Carmela; Sanderson, Gavin; Mahmud, Saadia; Wallace, M (Centre for Research in Education and Instructional Technologies, Taylor’s University, 2012)
This paper presents research from an Australian Learning and Teaching Council priority project which focuses on the assessment moderation practices between parent and partner universities in transnational partner universities. This paper addresses the challenges faced by transnational academic staff in ensuring comparable assessment standards. The data illuminates many issues of culture, language, relationships, trust, power and control. Using activity theory and its principles of contradictions, these issues are analysed in terms of Engestrom’s expanded mediated triangle. The components of subject, mediating tools, objects, rules, community and division of labour are interconnected and in constant dynamic interaction emphasising the social and contextualised nature of moderation practices and policies. Systemic tensions are bound to emerge between and among these components. This paper sets out to identify these systemic tensions or contradictionsfor their heuristic value and potential as the driving force for change, indicating points of intervention to improve assessment moderation practices and policies. Among the three indicated contradiction triads, some fundamental contradictions exist between subjectcommunity-object, subject-mediating tools-object and subject-division of labour-object.These help identify the weaknesses in the existing collaborative patterns and lack of efficacy of the mediating tools for ignoring the ‘culture of use’ of the tools and a clear understanding of roles and responsibilities on the ground.